PRIMARY BREAST TUBERCULOSIS MASTITIS MANIFESTED AS NON-HEALING ABSCESS - El-Helou, Etienne; Hoang, Huu; Pop, Catalin-Florin; Shall, Ammar; Zaiter, Manar; Naccour, Jessica; Ho, Xuan Dung; Nguyen, Van Cau (Mastology, 2026)
Primary breast tuberculosis is a rare extrapulmonary tuberculosis mainly affecting young women of childbearing age in endemic countries. Its incidence is increasing in immunocompromized and HIV-infected people and with the emergence of drug-resistant strains of Mycobacterium tuberculosis. There are no specific clinical signs suggestive of this disease, and it often presents as a hard mass or breast abscess. There is an overlap of features with other inflammatory, infectious, benign lesions, fat necrosis, and malignant neoplasms of the breast. The detection of Mycobacterium tuberculosis remains the gold standard for diagnosis. Several diagnostic modalities are used, with varying degrees of lack of sensitivity and specificity, and with a range of false negatives. A quarter of cases were treated solely on the basis of clinical, imaging, or histological suspicion, without confirmation of the diagnosis. Therefore, we report the case of a young Vietnamese woman who presented with a non-healing breast abscess and was diagnosed with breast tuberculosis based on the patient’s ethnicity, histological findings, lack of clinical response to conventional antibiotic therapy, and a good clinical response to antituberculosis treatment.